POLA KOMUNIKASI BUDAYA DALAM AKTIVITAS JUAL BELI PADA PASAR TRADISIONAL LIMBUNG KABUPATEN GOWA - Nurmawaddah , Nurmawaddah; Muliadi, Muliadi; Zelfia, Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2022)
This research started from the finding of communication phenomena in traditional markets. In the traditional market the process of buying and selling transactions with interpersonal communication (face to face) between the seller and the buyer. Bargaining in buying and selling in traditional markets is common in the process of transactions (payments) or even without transactions because there is no agreement between the seller and the buyer. The process of buying and selling transactions begins with greetings, the process of bargaining until the transaction is colored by conversations between the seller and the buyer that even leaves the main topic. The process in these stages forms a communication pattern. The formulation of the problem to be answered in this study is how the pattern of communication between sellers and buyers in buying and selling transactions in traditional markets is. This study examines the communication patterns of sellers and buyers in the transaction process in traditional markets. The focus in this research is the communication component in buying and selling transactions in traditional markets. Using the ethnographic method of communication, with participant observation and in-depth interviews with five seller informants and five buyer informants who were selected using a purposive sampling technique with predetermined criteria. The results of this study indicate that sellers and buyers in transactions use dyadic communication patterns, there is a symbolic interactionism model communication process between the seller and the buyer, the unique communication component is found in verbal (language) and non-verbal messages (clothing, touch, body language) and effects and context of communication. The effect of communication in the process of buying and selling transactions that can give birth to intimacy between the seller and the buyer. The context of communication is not only about the topic of buying and selling transactions, but also about other topics such as personal gossip, economics, education, religion, culture, social and even politics. This research requires further research with a different paradigm so that it can be further developed in an ethnographic communication research.